Serial alternative response training as intervention for target response resurgence. Issue 4 (24th September 2015) - Lambert, Joseph M.; Bloom, Sarah E.; Samaha, Andrew L.; Dayton, Elizabeth; Rodewald, Andrew M.
Abstract : Failure to reinforce appropriate behavior could result in resurgence of previously extinguished problem behavior and degradation of previously effective treatments such as differential reinforcement of alternative behavior (DRA). We analyzed arbitrary responses (i.e., switch flipping) exhibited by 3 adults with developmental disabilities to compare the effect of a traditional DRA intervention against the effect of a serial DRA intervention on the magnitude of target response resurgence using a 2‐component multiple schedule. The target response served as an analogue to problem behavior, and alternative responses served as analogues to socially appropriate alternative responses. In all cases, the percentage of total responding allocated toward target response resurgence was less in the serial DRA component than in the traditional DRA component. Furthermore, we observed both reversion and recency for 2 of 3 subjects. Our data provide preliminary evidence suggesting that serial DRA may produce more durable and desirable outcomes than traditional DRA.